Transplantatıon Of An Invertedly Impacted Upper Central Incısor - Celal Tümer; Tülin Uğur; Kemal Şençift; Aslı Telli (Turkish Journal of Orthodontics, 1997)

(untitled)
Impacted tooth is impeded or blocked usually by an adjacent tooth or pathology. Impaction is suspected clinically when opposing tooth is erupted and is almost certain when the same tooth of the opposite side is present. Supernumerary teeth are common in the maxillary incisor region. Those developing between the two central incisors are called ‘mesiodens’, occuring single or in pairs. Impacted central incisors, which are in inverted position with mesiodens are seen very rarely. This case report presents the preoperative, operative and postoperative findings of transplantation of an inverted central in a 13-year-old boy.